1994
DOI: 10.1002/j.1460-2075.1994.tb06613.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequences within the poliovirus internal ribosome entry segment control viral RNA synthesis.

Abstract: The 5′ untranslated region of poliovirus RNA has been reported to possess two functional elements: (i) the 5′ proximal 88 nucleotides form a cloverleaf structure implicated in positive‐strand RNA synthesis during viral replication, and (ii) nucleotides 134 to at least 556 function as a highly structured internal ribosome entry segment (IRES) during cap‐independent, internal initiation of translation. We show here that the IRES itself is bifunctional and contains sequences necessary for viral RNA synthesis per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
90
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(97 citation statements)
references
References 46 publications
5
90
1
1
Order By: Relevance
“…1 left, motif A). We found that for PV this motif is not a prerequisite for efficient IRES-driven translation or virus viability (Borman et al, 1994). Instead, the functional sequence conforms to an NYRA consensus.…”
Section: Molecular Genetic Approach To Assess Poliovirus Ires Structumentioning
confidence: 83%
“…1 left, motif A). We found that for PV this motif is not a prerequisite for efficient IRES-driven translation or virus viability (Borman et al, 1994). Instead, the functional sequence conforms to an NYRA consensus.…”
Section: Molecular Genetic Approach To Assess Poliovirus Ires Structumentioning
confidence: 83%
“…In vivo analysis of IRES activity of GNRA tetraloop mutants+ Plasmids containing the indicated tetraloop sequences within the EMCV IRES cDNA inserted into a CAT/LUC reporter vector were transfected into vTF7-3-infected 293 cells+ After 20 h, cell extracts were prepared and analyzed by SDS-PAGE and immunoblotting using rabbit anti-CAT (upper panel) and rabbit anti-LUC (middle panel) antibodies followed by peroxidase-labeled anti-rabbit IgG+ Detection was achieved using chemiluminescence reagents+ The same extracts were also assayed for LUC activity (lower panel)+ ever, as demonstrated in Figure 6, even the low level of sFv expression achieved by some of these IRES elements was sufficient to achieve efficient cell selection+ Thus it appears that the selection system has a threshold level of sFv expression required to achieve selection+ However, it is most likely to yield IRES elements with high activity, as 28 of the 37 sequences selected (representing 75%) contained IRES elements in which the GNRA tetraloop sequence fitted the RNRA consensus required for optimal activity+ The individual assay within cells of each of the functional mutants, as defined by their activity in the TNT reactions, demonstrated that the low-level activity exhibited by some of these IRES elements was sufficient to permit efficient cell selection and thus justified their classification as functional+ This assay also demonstrated that the mutant IRES elements were not selected as a result of cotransfection with, or complementation by, other functional IRES elements+ We have shown previously that mutant EMCV IRES elements can be complemented in trans (e+g+, Roberts & Belsham, 1997) but the individual assay of the different mutant elements ruled out this explanation+ Previous work (Kaminski et al+, 1994;Lopez de Quinto & Martinez-Salas, 1997;Roberts & Belsham, 1997) had served to demonstrate the functional importance of the conserved GNRA motif in the picornavirus IRES elements+ However, even the most extensive of these studies only examined the activities of a small fraction of the 256 potential mutants+ The studies presented here illustrate the value of a selection system+ It was possible to select functional IRES elements from a large pool of tetraloop mutants+ Some of the recovered sequences contained second site changes close to the mutagenized tetraloop sequence; however each of these changes appeared to be detrimental to some degree+ Presumably these second site mutations were introduced during the PCR that generated the pool of mutant fragments+ It would clearly be possible to introduce the tetraloop mutations into a complete infectious copy or a virus replicon and then to analyze the sequences that are most efficiently replicated+ Indeed many studies with picornaviruses have introduced mutations into fulllength infectious cDNAs and then selected for functional viruses (e+g+, Haller & Semler, 1992;Pilipenko et al+, 1992;Macadam et al+, 1994)+ No such studies have been reported with respect to the GNRA motif+ It should be noted that such a system fails to separate effects of mutations within the 59 NCR on replication that may be distinct from those on translation alone (see Borman et al+, 1994)+ The system used here clearly separates these two processes+ Furthermore, once RNA replication is involved, rapid evolution toward an optimum sequence is facilitated that may there...…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that the cellular IRESs are presumably used only for translation while viral IRESs have other functions as well, e.g. replication (52).…”
Section: Discussionmentioning
confidence: 99%